Peran Senyawa Bioaktif Tumbuhan untuk Penyakit Degeneratif : Tinjauan Kimia Medisinal - Agis Difa Maharan; Saeful Amin; Nova Noor Fauzan; Nova Sopiyanti (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
Degenerative diseases, such as Alzheimer's, diabetes mellitus, and cancer, are global health challenges whose prevalence increases with increasing life expectancy. Phytochemicals, bioactive compounds found in plants, have shown potential in preventing and inhibiting the development of these diseases. Compounds such as flavonoids, polyphenols, and glucosinolates have antioxidant, anti-inflammatory, and neuroprotective activities that can protect these body cells from oxidative damage and chronic inflammation. This study suggests that consuming phytochemical-rich foods, such as cruciferous vegetables, pigmented fruits, and certain spices, contributes to a reduced risk of degenerative diseases.